2009
DOI: 10.1007/s00044-009-9284-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure, and anticancer properties of cyclic monocarbonyl analogs of curcumin

Abstract: A series of novel indan-2-one and dibenzylidenepiperidin-4-one compounds were synthesized and screened for anticancer activities. The compounds are symmetrical and they have conjugated double bonds. They closely resemble the curcumin analogs which are found to possess anticancer properties. The structure of the compounds was confirmed by single crystal study and wherever the compound is a powder, the structures were confirmed by spectral data (IR, NMR, and Mass).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…[5][6][7]25] Based on the encouraging results, we developed this method further. Herein, we finely tuned the reaction of b-naphthol with aromatic aldehydes and ethanolic ammonium acetate.…”
Section: Resultsmentioning
confidence: 97%
“…[5][6][7]25] Based on the encouraging results, we developed this method further. Herein, we finely tuned the reaction of b-naphthol with aromatic aldehydes and ethanolic ammonium acetate.…”
Section: Resultsmentioning
confidence: 97%
“…24) A recent study demonstrated that curcuminrelated compounds with an inden-2-one had enhanced activity and lower cytoxicity. 25,26) In the present study, seven curcumin-related compounds using inden-2-one as a linker and various substituents on the aryl rings (Chart 1) were synthesized and evaluated for their effects against four human cancer cell lines. These compounds were previously not reported except for IND-1.…”
mentioning
confidence: 99%
“…The highlight is that none of them are toxic. 13 The results show that this does not merely reveal the protocol but also provides a potential green alternative to traditional method and also for further drug development. Mild reaction condition, cost efficiency, simplicity in operations and separation, one-pot fashion are the significant features of this protocol.…”
Section: Resultsmentioning
confidence: 87%
“…11,12 Recently our research group found the anti-cancer activity of its related analogues. 13 Thus, the synthesis of α,α'-bis(substituted benzylidene)cycloalkanones has attracted the attention of authors. Cross aldol condensation is classically carried out using acid or base.…”
Section: Introductionmentioning
confidence: 99%